2021
DOI: 10.1016/j.arth.2020.09.050
|View full text |Cite
|
Sign up to set email alerts
|

General vs Neuraxial Anesthesia in Direct Anterior Approach Total Hip Arthroplasty: Effect on Length of Stay and Early Pain Control

Abstract: Background. Recent literature has suggested some benefits for neuraxial anesthesia (NA) as an alternative for general anesthesia (GA) for primary total hip arthroplasty patients. We examined the impact of NA versus GA on outcomes for patients undergoing direct anterior (DA) approach total hip arthroplasty (THA) in an institution with established rapid recovery protocols. Methods. Retrospective review was conducted for 500 consecutive THA patients from a single institution. Univariate analysis and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Our series supports this claim and demonstrated a reduction in PACU length of stay of 25 minutes as well as a modest reduction in hospital length of stay of 0.1 day in patients treated with spinal anesthesia. Although small, this difference of 0.1 day is comparable with prior investigations that demonstrated spinal anesthesia’s association with significant reductions in hospital length of stay ranging from 0.1 to 0.6 day 29-32 . Likewise, aggregate data from the largest systematic review evaluating the outcomes of anesthetic techniques in total joint arthroplasties have suggested that spinal anesthesia afforded a 0.4-day reduction in hospital length of stay 12 .…”
Section: Discussionsupporting
confidence: 82%
“…Our series supports this claim and demonstrated a reduction in PACU length of stay of 25 minutes as well as a modest reduction in hospital length of stay of 0.1 day in patients treated with spinal anesthesia. Although small, this difference of 0.1 day is comparable with prior investigations that demonstrated spinal anesthesia’s association with significant reductions in hospital length of stay ranging from 0.1 to 0.6 day 29-32 . Likewise, aggregate data from the largest systematic review evaluating the outcomes of anesthetic techniques in total joint arthroplasties have suggested that spinal anesthesia afforded a 0.4-day reduction in hospital length of stay 12 .…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that neuraxial anesthesia is associated with a reduction in length of hospital stay when compared with general anesthesia 13 24 25. For example, a recent study by Kelly et al 29 comparing neuraxial to general anesthesia in 500 total hip arthroplasty patients at their institution found a significant reduction in length of hospital stay in the neuraxial group (32.7 hours, SD 14.8 vs 38.1 hours, SD 24, p=0.003). However, these studies did not exclusively look at outpatient total joint patients where patients are expected to be discharged from the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we also found that the MMSE score in the Outside group was lower than that in the Inside group at 6, 24, and 48 h postoperatively, while the incidence of POCD in the Outside group was higher than that in the Inside group at 6, 24, and 48 h postoperatively. Anesthesia protocol is an important factor impacting postoperative pain and the incidence of POCD ( 23 , 24 ). Our results have shown that the inside approach of the FICB was more effective in anesthetizing patients than the outside approach.…”
Section: Discussionmentioning
confidence: 99%